Kesepadanan Tekstual Konstruksi Tema Rema dalam Takarir Bahasa Arab Film Mitos Nyawur: Studi Kasus Penerjemahan Purbalingga / Textual Equivalence of Theme and Rheme in the Arabic Subtitle of Nyawur Mith Movie: Case Study in Purbalingga – Arabic Translatio - Anis, Muhammad Yunus (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
This study will examine the textual equivalence of the construction of Theme and Rheme in the subtitle of the film “Nyawur”, Purbalingga Myth, (Purbalingga (L1) – Arabic (L2)). The data in this study were taken from the subtitle of the short film Myth “Nyawur” (sowing salt in the hope that the rain would stop) in VIU. Films related to these myths use subtitles in Arabic. Some of these films use local languages ​​that contain mythical terms. The formulation of the first problem in this study is how the textual equivalence of the translation of Themes and Rheme in the short films screened in VIU. Meanwhile, the second problem is how the strategy is used in translating the construction of Themes and Rhemes in the short film. This study uses a qualitative descriptive method using three main stages, namely: (1) data collection using the observation method, in this case the units of language are one of the core studies to see the textual equivalence in the local language with Arabic subtitles, (2) data analysis using the equivalence method to see and measure the lexical equivalence of the construction of Themes and Rhemes between the source language and the target language, along with what strategies are used in translating the myth. The final stage (3) reports the results by describing the textual equivalence of the construction of Themes and Rhemes in the source language and the target language. This study concludes that the translation of subtitles tends to be in the target language (reader oriented). This research is expected to have an impact in the study of Arabic translation, in particular improving the quality of translation of Arabic subtitles in local films in Indonesia so that they can be enjoyed by Arabic speakers. مستلخص ستدرس هذه الدراسة التكافؤ النصي لبناءTheme and Rheme في العنوان الفرعي لفيلم “Nyawur" ، البيانات الواردة في هذه الدراسة مأخوذة من العنوان الفرعي للفيلم القصير "نياور" (بذر الملح على أمل أن يتوقف المطر) في VIU. تستخدم بعض هذه الأفلام لغات محلية تحتوي على مصطلحات أسطورية. تتمثل صياغة المشكلة الأولى في هذه الدراسة في كيفية التكافؤ النصي لترجمة Theme and Rheme في الأفلام القصيرة التي تم عرضها في VIU. المشكلة الثانية هي كيفية استخدام الإستراتيجية في ترجمة بناء Theme and Rheme في الفيلم القصير. تستخدم هذه الدراسة المنهج الوصفي النوعي باستخدام ثلاث مراحل رئيسية وهي: (1) جمع البيانات باستخدام طريقة الملاحظة ، في هذه الحالة تعتبر وحدات اللغة واحدة من الدراسات الأساسية لمعرفة التكافؤ النصي في اللغة المحلية مع الترجمة العربية. (2) تحليل البيانات باستخدام طريقة التكافؤ لمعرفة وقياس التكافؤ المعجمي لبناء Theme and Rheme بين لغة المصدر واللغة الهدف ، جنبًا إلى جنب مع الاستراتيجيات المستخدمة في ترجمة الأسطورة. تُبلغ المرحلة النهائية (3) عن النتائج من خلال وصف التكافؤ النصي لبناء Theme and Rheme في اللغة المصدر واللغة الهدف. خلصت هذه الدراسة إلى أن ترجمة العنوان الفرعي للفيلم تميل إلى أن تكون باللغة الهدف (موجه للقارئ). من المتوقع أن يكون لهذا البحث تأثير في دراسة الترجمة العربية ، ولا سيما تحسين جودة ترجمة الأفلام العربية في إندونيسيا حتى يستمتع بها الناطقون باللغة العربية. Theme - Rheme ;الترجمة العربية ;VIU الكلمات المفتاحية : العنوان الفرعي؛ ترجمة الأسطورة